The influence of service quality website towards customer loyalty on Maybank online banking in University Malaysia Kelantan (UMK) Kampus Kota,Pengkalan Chepa - Mohamad Amin, Mohammad Adli; Elias, Siti Norasyikin; Therumurthy, Thulasi; Loo, Chee Soon (2015)
The aim of this study was to investigate the relationship between customer loyalty towards Maybank online banking among UMK students in kampuskotaPengkalanChepa. This study suggests that service quality, perceived value, trust, habits, and the reputation of having a relationship with customer loyalty towards Maybank online banking. The study was conducted in the city of UMK kampuskotaPengkalanChepa Kelantan, Malaysia. Pearson correlation and multiple regressions were used to test the proposed hypotheses and research questions. The study found that the service quality, perceived value, trust, habit, and reputation that has a strong relationship with Maybank customer loyalty to online banking. The findings in this study will assist the students in understanding the Maybank banking and the main reasons why customers choose to be faithful to the Maybank online banking and they can make improvements in their service.